Periodontal Antibodies and All-Cause and Cardiovascular Disease Mortality. (January 2020) - Qi, J.; Zihang, Z.; Zhang, J.; Park, Y.M.; Shrestha, D.; Jianling, B.; Merchant, A.T.
Periodontitis is positively linked to cardiovascular disease (CVD), diabetes, cancer, and increased mortality. Empirically derived clusters of IgG antibodies against 19 selected periodontal microorganisms have been associated with hyperglycemia. We further investigated associations between these serum IgG antibody clusters and all-cause and CVD mortality in a representative US population. Participants free of CVD and cancer and aged ≥40 y at baseline ( N = 6, 491) from the Third National Health and Nutrition Examination Survey (1988 to 1994) were followed up until December 31, 2011. Antibodies were categorized into 4 clusters: red-green, orange-red, yellow-orange, and orange-blue. Over a 23-y follow-up, 2, 702 deaths occurred, including 810 CVD-related deaths. In fully adjusted Cox proportional hazard models, the red-green cluster was positively associated with all-cause mortality (tertile 3 vs. tertile 1: hazard ratio [HR] = 1.43, 95% CI = 1.08 to 1.90, P = 0.015). The yellow-orange cluster was inversely associated with all-cause mortality (tertile 3 vs. tertile 1: HR = 0.78, 95% CI = 0.63 to 0.97, P = 0.028) and CVD mortality (tertile 2 vs. tertile 1: HR = 0.57, 95% CI = 0.42 to 0.77, P = 0.005). The orange-blue cluster (composed of antibodies against Eubacterium nodatum and Actinomyces naeslundii ) was inversely associated with all-cause mortality (tertile 3 vs. tertile 1: HR = 0.65, 95% CI = 0.55 to 0.78, P < 0.0001) and CVD mortality (tertile 3 vs. tertile 1: HR = 0.65, 95% CI = 0.47 to 0.88, P = 0.007). These antibodies could predict prognosis or be potential intervention targets to prevent systemic effects of periodontal disease if further studies establish a causal relationship.